The antiproliferative potential and mechanism of action of metformin in MCF-7 cells - Zhibek Bekezhankyzy; Sholpan Nurzhan; Nurken Berdigaliyev; Shynggys Sergazy; Tilektes Maulenkul; Mohamad Aljofan (Future Science OA)
Aim: The current study aimed to investigate the potential antiproliferative activity of metformin, the effective concentration range, and the mechanism of action. Materials & methods: Human breast cancer cells, MCF-7 were treated with a serial dilution of metformin (10–150 μM) for 24 and 48 h. Potential antiproliferative activity of metformin and its ability in inducing cellular apoptosis and autophagy were also investigated. Results: Metformin inhibited MCF-7 proliferation in a concentration and time dependent manner, with 80 μM as the most effective concentration. Compared with nontreated cells, metformin induced significant levels of autophagy and apoptosis, which were confirmed by the reduction of mTOR and BCL-2 protein expression. Conclusion: The study confirms the antiproliferative activity of metformin, which may likely occur through AMPK signaling pathway.